2015
DOI: 10.1097/brs.0000000000000768
|View full text |Cite
|
Sign up to set email alerts
|

A Zero-Profile Anchored Spacer in Multilevel Cervical Anterior Interbody Fusion

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 23 publications
3
35
0
2
Order By: Relevance
“…The success of the ACDF relies on a thorough decompression and achievement of solid intervertebral fusion. Biomechanical studies have revealed that the self-locking stand-alone cage provides less stiffness of cervical spine as locking plate does in 2 or 3-level instrumentation [14,15]. But high fusion rate can be achieved using these kinds of cages for the treatment of single-level, double-level, and even three-level cervical spondylopathy (Table 3) [7][8][9][10][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The success of the ACDF relies on a thorough decompression and achievement of solid intervertebral fusion. Biomechanical studies have revealed that the self-locking stand-alone cage provides less stiffness of cervical spine as locking plate does in 2 or 3-level instrumentation [14,15]. But high fusion rate can be achieved using these kinds of cages for the treatment of single-level, double-level, and even three-level cervical spondylopathy (Table 3) [7][8][9][10][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The titanium alloy plate was positioned in anterior vertebral line and the anterior intervertebral disk height might decrease less than posterior; in addition, the CL was restored by pulling the involved vertebrae towards the prebent lordotic ventral plate, which could make the segmental angle more improved [6]. While the zero-profile anchored spacer, consisting of a cage and single or two anchoring clips, showed less ability to restore CL than ACP [18]. On the other hand, a larger improvement on OPCL added more weights on CL reconstruction in three-level ACDF.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential factor driving this observed difference may be due to external pressures in the ambulatory surgery center setting, wherein shorter operative times and a more maximized use of scheduled operating room time are incentivized because of financial incentives and staff leaving early. In addition, newer standalone ACDF systems allow for significantly reduced surgical times as compared with traditional plate and screw systems, despite reductions in biomechanical stiffness, which may lead to an increased risk of pseudarthrosis [26,27]. Adjacent segment disease may also contribute to these higher rates of revision surgery, which is a well-known long-term complication of the ACDF procedure.…”
Section: Discussionmentioning
confidence: 99%